Prime times : a handbook for excellence in infant and toddler programs - Greenman, James T., 1949- (Addison Wesely Longman, 1997)
This book is divided into six parts: The context of good care: Good organisations for infant and toddler care; Organising the program; Quality caregiving; Quality learning; Good places for adults; and Staying good: Evaluation and quality control.